Exploring LiDAR as a Scalable Photonic Alternative to Turbidimeters for Water Turbidity Monitoring - Nur Aina Athirah Mohd Nizar; Juliza Jamaludin; Marinah Othman (IEEE Photonics Society, 2026)
Non-Indexed Publication